An unusual growth in the nail matrix: A case of superficial acral fibromyxoma - Genevieve Ho; Caroline Kurek; David Stewart; Linda K. Martin (Skin Health and Disease, 2022)
Abstract We describe a case of superficial acral fibromyxoma arising within the germinal matrix of the index finger. This is an uncommon localisation of this relatively newly described benign soft tissue tumour. Herein, we discuss the varied clinical presentation, distinguishing histopathological features and important differential diagnoses for this condition.